2014
DOI: 10.24925/turjaf.v3i2.74-79.179
|View full text |Cite
|
Sign up to set email alerts
|

Niğde İli Keçi Yetiştiriciliğinin Yapısal Özellikleri ve Sorunları Üzerine Bir Araştırma

Abstract: Niğde ili keçicilik işletmelerinin mevcut durumu, yapısal özellikleri ve bu işletmelerin öncelikli sorunlarının ortaya konulması amacıyla yürütülmüştür. Bu amaçla rastgele seçilen 38 adet keçi işletmesinde yetiştiricilerle yüz-yüze anket çalışması yapılmıştır. Anket soruları; işletmelerin genel yapısı ile yetiştirme faaliyetlerini ortaya koyabilecek ve ayrıca yetiştiricilerin öncelikli sorunları ile memnuniyet durumlarını ölçebilecek şekilde belirlenmiştir. Anket sonuçları, keçi işletmesi sahiplerinin %89,5'in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 2 publications
1
2
0
Order By: Relevance
“…The rate of those who receive government support and bank credit support from agricultural supports is 70.9%. Among the production problems identified in the study, feed supply and high feed prices are similar to the problems reported by Karadaş (2018) in Hakkari and Savaş et al (2019a) in Igdir province and Ceyhan et al (2020) in their study.…”
Section: Figure 1 Problems Encountered In Animal Husbandrysupporting
confidence: 86%
“…The rate of those who receive government support and bank credit support from agricultural supports is 70.9%. Among the production problems identified in the study, feed supply and high feed prices are similar to the problems reported by Karadaş (2018) in Hakkari and Savaş et al (2019a) in Igdir province and Ceyhan et al (2020) in their study.…”
Section: Figure 1 Problems Encountered In Animal Husbandrysupporting
confidence: 86%
“…As a result of the study, it was reported that 88% of those working in the agricultural sector were concerned about harvesting and sales and that these concerns were mostly (35.6%) due to price instability (Uğur & Buruklar, 2022). In our country, factors such as the low level of education and income of ovine breeders in general and breeding by very small family enterprises with production techniques that continue from father to son cause problems in the input supply of enterprises and the marketing of products (Sarıca et al, 2004;Ceyhan et al, 2015aCeyhan et al, , 2015bKandemir et al, 2015). The education, age, and gender findings obtained in the study were found to be similar to those reported in the literature (Ateş & Çam, 2022;Uğur & Buruklar, 2022).…”
Section: Socio-economic Status Of Breedersmentioning
confidence: 90%
“…The most important problem in sheep breeding enterprises is labor and feed expenses. In addition to these problems, the fact that the owners do not have sufficient knowledge about lamb growth and fattening and that they generally provide breeding from within the enterprise is among the general breeding problems (Ceyhan et al, 2015a(Ceyhan et al, , 2015b.…”
Section: Breeding Practicesmentioning
confidence: 99%